2022
DOI: 10.3389/fphar.2022.888300
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Peel Extract Decreases Plaque Necrosis and Advanced Atherosclerosis Progression in Apoe-/- Mice

Abstract: Atherosclerosis is a chronic lipid-driven inflammatory condition of the arteries and is a leading cause of stroke, myocardial infarction, and other peripheral arterial diseases. Plant products rich in polyphenols such as pomegranate juice and peel extract are known to have beneficial effects in suppressing atherogenesis. However, the mechanism of action and its effect on advanced atherosclerosis progression which results in adverse clinical outcomes are not well understood. Herein, we use a standardized hydroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
1
8
0
2
Order By: Relevance
“…In conclusion, we showed that Brussels chicory can increase plaque stability in the aorta, at least in part through improving oxidative stress within plaques by inhibition of NOX and uncoupled eNOS-mediated free radical production in male Apoe −/− mice. Together with other works [ 36 , 37 , 38 , 39 , 40 , 41 ], our findings allow us to call for a re-visiting to the potential of antioxidant therapy in preventing cardiovascular disease events.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In conclusion, we showed that Brussels chicory can increase plaque stability in the aorta, at least in part through improving oxidative stress within plaques by inhibition of NOX and uncoupled eNOS-mediated free radical production in male Apoe −/− mice. Together with other works [ 36 , 37 , 38 , 39 , 40 , 41 ], our findings allow us to call for a re-visiting to the potential of antioxidant therapy in preventing cardiovascular disease events.…”
Section: Discussionsupporting
confidence: 79%
“…In addition to Brussels chicory, improving oxidative stress through dietary supplementation with individual polyphenols or polyphenols-rich extracts (e.g., anthocyanins [ 36 , 37 ], epigallocatechin gallate [ 38 ], protocatechuic acid [ 39 ], pomegranate peel extract [ 40 ]) or genetic modulation with increased GSH in macrophages [ 41 ] were associated with increased stability of advanced plaques in Apoe −/− mice. More importantly, a small clinical trial study shows that drinking pomegranate juice rich in polyphenols can not only halt the progression of established atherosclerosis but actually reverse it [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…O estudo randomizado foi feito em animais com oito semanas de idade envolvendo machos e fêmeas alimentados com uma dieta do tipo ocidental e foi observada diminuição da placa de necrose, aumento do colágeno nas lesões e de modo geral uma melhora considerável no perfil metabólico. De acordo com os resultados foi possível concluir que os polifenóis presentes na romã desempenham sua atividade na redução da placa aterosclerótica por meio do aumento de morte celular lesional em consonância com as células que já estão sendo suprimidas (Manickam et al, 2022).…”
Section: Resultsunclassified
“…artigos, sendo eles(Benchagra et al, 2021),(Atrahimovich et al, 2016),(Manickam et al, 2022),(Aviram e Rosenblat, 2013),(Huwait et al, 2022),(Anwaier et al, 2021) e apenas 1 em português(Aviram et al, 2000), como apresentado no quadro a seguir (Quadro 1).…”
unclassified
“…In the context of the topic of review, the juice at a concentration of 100 mg/kg/day and 300 mg/kg/day in Wistar rats was also found to inhibit ACE rendering it non-active alongside the antioxidant activity to counter the angiotensin-II activity (Mohan et al, 2010).The dry skin extract also showed significant improvements in endothelial dysfunction with the activation of the protein kinase B/eNOS signaling and reducing vasculitis (Vilahur et al, 2015). Another hydroethanolic extract of the peel showed improvement in the plaque necrosis phase of CHD along with improvements in harmful lipid parameters and systemic inflammation (Manickam et al, 2022). B2.…”
Section: Pharmacological Agentsmentioning
confidence: 99%